2016
DOI: 10.1002/chem.201603765
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 1,2‐Dioxetanes as Thermochemiluminescent Labels for Ultrasensitive Bioassays: Rational Prediction of Olefin Photooxygenation Outcome by Using a Chemometric Approach

Abstract: Great interest in new thermochemiluminescent (TCL) molecules, for example, in bioanalytical assays, has prompted the design and synthesis of a small library of more than 30 olefins to be subjected to photooxygenation, with the aim of obtaining new 1,2-dioxetane-based TCL labels with optimized properties. Fluorine atoms on the acridan system remarkably stabilize 1,2-dioxetanes when they are located in the 3- and/or 6-position (4 h and 4 i). On the other hand, 2,7-difluorinated acridan dioxetane (4 j) showed a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 162 publications
1
25
1
1
Order By: Relevance
“…We found that the lnA and Ea activation parameters of 1,2-dioxetane 1 in CN-PPV Pdots were 21.1 ± 2.4 kcal mol −1 K −1 and 21.4 ± 3.1 respectively. Such values were significantly lower than the values measured for the 1,2-dioxetane 1 in the solid state, 27 as already found for compound 1 entrapped in silica NPs. However, the thermal decomposition reaction in silica NPs was much faster than that in Pdots.…”
Section: Resultscontrasting
confidence: 56%
See 2 more Smart Citations
“…We found that the lnA and Ea activation parameters of 1,2-dioxetane 1 in CN-PPV Pdots were 21.1 ± 2.4 kcal mol −1 K −1 and 21.4 ± 3.1 respectively. Such values were significantly lower than the values measured for the 1,2-dioxetane 1 in the solid state, 27 as already found for compound 1 entrapped in silica NPs. However, the thermal decomposition reaction in silica NPs was much faster than that in Pdots.…”
Section: Resultscontrasting
confidence: 56%
“…Substrate 1 was synthesized following a previously reported procedure (for more details see Supporting Information). 27 The 1,2-dioxetane 1 -doped Pdots were prepared following a co-nanoprecipitation method. 43 In a typical procedure, stock solutions of CN-PPV (1 mg/mL), PS-COOH (1 mg/mL) and substrate 1 (2 mg/mL) in THF were prepared.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…If these chemiluminophores are chemically modified to be stable at room temperature, their decomposition can be induced by heating or by application of mechanical force, and the respective phenomena are referred to as thermo- and mechanochemiluminescence. It was demonstrated recently that mechanochemiluminescent polymers can be prepared by incorporating mechanoluminophores in their polymer backbone 5,6 , and thermochemiluminescence was also accomplished by heating of deposited nanoparticles 79 and microcrystalline powder 10 . Chemiluminescence in the pure macroscopic solid state, however, was deemed unfeasible due to the very limited ability of molecules for diffusion required for their reaction and the anticipated low quantum yields.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the Quintavalla and Lombardo group synthesized a small library of more than 30 alkenes to be subjected to photooxygenation, with the aim of obtaining new 1,2-dioxetane-based TCL labels with optimized properties. 115 Furthermore, to verify the capability of the lithium diisopropylamide (LDA) model to predict the reactivity of new compounds with singlet oxygen, the fluorenylalkene 171 (central five-membered ring) and the new alkene 173 (central seven-membered ring) were prepared (Scheme 28). The fluorenyl-derived alkene 171 was predicted to be reactive with a raw canonical score of 30.8 due to an almost completely planar arrangement of the aro-matic rings with respect to the plane defined by the C=C bond (ϕ 1 , ϕ 2 = 159.8°), whereas 5-dibenzosuberenone-derived alkene 173 was predicted to be unreactive with a raw canonical score of -39.9 due to its significantly smaller dihedral angles ϕ 1 and ϕ 2 (113.3°).…”
Section: Olefination Reactions Via the Carbonyl Groupmentioning
confidence: 99%